2016
DOI: 10.1038/ejhg.2016.131
|View full text |Cite
|
Sign up to set email alerts
|

A cross-ethnic survey of CFB and SLC44A4, Indian ulcerative colitis GWAS hits, underscores their potential role in disease susceptibility

Abstract: The first ever genome-wide association study (GWAS) of ulcerative colitis in genetically distinct north Indian population identified two novel genes namely CFB and SLC44A4. Considering their biological relevance, we investigated allelic/genetic heterogeneity in these genes among ulcerative colitis cohorts of north Indian, Japanese and Dutch origin using high-density ImmunoChip casecontrol genotype data. Comparative linkage disequilibrium profiling and test of association were performed. Of the 28 CFB SNPs, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…IBD patients exhibit increased levels of circulating CFB ( Nielsen et al, 1978 ; Campbell et al, 1982 ; Adinolfi and Lehner, 1988 ) and a similar increase of serum CFB has been observed in DSS-induced and bisphenol A (BPA)-induced experimental colitis in mice ( Huang et al, 2022 ). More recently, genome-wide association studies (GWAS) have identified one SNP (rs4151657) at the CFB locus, which represents a risk variant for UC susceptibility ( Juyal et al, 2015 ; Gupta et al, 2016 ; Shi et al, 2020 ; Mortlock et al, 2023 ). The presence of the rs4151651 SNP was associated with increased CFB expression, and CFB expression was shown to correlate with disease activity ( Shi et al, 2020 ; Mortlock et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…IBD patients exhibit increased levels of circulating CFB ( Nielsen et al, 1978 ; Campbell et al, 1982 ; Adinolfi and Lehner, 1988 ) and a similar increase of serum CFB has been observed in DSS-induced and bisphenol A (BPA)-induced experimental colitis in mice ( Huang et al, 2022 ). More recently, genome-wide association studies (GWAS) have identified one SNP (rs4151657) at the CFB locus, which represents a risk variant for UC susceptibility ( Juyal et al, 2015 ; Gupta et al, 2016 ; Shi et al, 2020 ; Mortlock et al, 2023 ). The presence of the rs4151651 SNP was associated with increased CFB expression, and CFB expression was shown to correlate with disease activity ( Shi et al, 2020 ; Mortlock et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These autoimmune diseases responsible genes might be critical for the development of CD. Recently, study found that CXCL5 [454], S100A12 [455], OSM (oncostatin M) [456], LRG1 [457], LCN2 [458], CXCL1 [459], S100A9 [460], IFITM1 [461], XBP1 [462], MMP3 [457], IFITM3 [463], IL1B [464], GBP5 [465], HGF (hepatocyte growth factor) [466], CXCL9 [467], SLC11A1 [468], IL1RN [469], STAT1 [470], CYP27B1 [471], MMP1 [472], SOCS3 [473], TLR8 [474], CD55 [475], CCL28 [476], FCGR2A [477], CCL2 [478], CFB (complement factor B) [479], CD14 [480], GPR84 [481], PCSK9 [482], FOXP3 [483], LPL (lipoprotein lipase) [484], IL1R2 [485], TLR2 [486], MEFV (MEFV innate immuity regulator, pyrin) [487], VWF (von Willebrand factor) [488], NOD2 [489], DMBT1 [490], HSPA6 [491], TIMP1 [492], ICAM1 [493], EGR1 [494], CCL11 [495], IFNG (interferon gamma) [496], APOE (apolipoprotein E) [497] FGR (FGR proto-oncogene, Src family tyrosine kinase) [498], IL6 [499], SPP1 [192], IL11 [500], RNF186 [501], MMP2 [502], CD24 [503], SPHK1 [504], GZMB (granzyme B) [505], MUC5AC [506], SERPINA3 [507], TWIST1 [508], PLAU (plasminogen activator, urokinase) [509], CA2 [510], CA9 [510], CTLA4 [511], PADI4 [512], MMP13 [513], MPO (myeloperoxidase) [244], LEFTY1 [514], CA1 [515], MMP7 [513], ABCG2 [516], CYP2J2 [517], AICDA (activation induced cytidine deaminase) [518], CYP2D6 [519], CYP3A5 [52...…”
Section: Discussionmentioning
confidence: 99%
“…The SLC44A4 (solute carrier family 44 member 4) gene located at 6p21.33 encodes human thiamine pyrophosphate transporter (TPPT), which is involved in the uptake of choline by cholinergic neurons. The SLC44A4 gene was reported to be associated with ulcerative colitis (UC) susceptibility in the Indian, Japanese, and Chinese populations ( Gupta and Thelma, 2016 ; Gupta et al, 2016 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%